1983
DOI: 10.5144/0256-4947.1983.21
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Debilitated Child with Massive Wilms' Tumor

Abstract: Five Saudi Arabian children, 2 to 6 years of age, presented with far advanced Wilms' tumors impairing staging and treatment according to the recommendations of the American National Wilms' Tumor Study Group (NWTSG). These patients were not eligible for general anesthesia and surgery because of their poor general condition. The tumours were locally advanced with or without dissemination. The term "Stage S" to signify special was introduced to describe these patients. Additionally, a protocol was implemented inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…6 Furthermore, in a patient whose tumor is relatively advanced and therefore unsuitable for surgical resection, fine needle aspiration biopsy (FNAB) diagnosis may help in initiating proper chemotherapy or radiation therapy in order to reduce the tumor size, thus rendering it amenable to surgical resection. 7 Several recent studies have shown that FNAB may be an extremely useful technique for diagnosing renal neoplasms. [8][9][10][11][12][13][14][15][16][17] However, definitive FNAB diagnosis of these tumors requires a thorough knowledge of the various histologic patterns encountered in these tumors and a clear understanding of corresponding histologic and cytologic correlations.…”
mentioning
confidence: 99%
“…6 Furthermore, in a patient whose tumor is relatively advanced and therefore unsuitable for surgical resection, fine needle aspiration biopsy (FNAB) diagnosis may help in initiating proper chemotherapy or radiation therapy in order to reduce the tumor size, thus rendering it amenable to surgical resection. 7 Several recent studies have shown that FNAB may be an extremely useful technique for diagnosing renal neoplasms. [8][9][10][11][12][13][14][15][16][17] However, definitive FNAB diagnosis of these tumors requires a thorough knowledge of the various histologic patterns encountered in these tumors and a clear understanding of corresponding histologic and cytologic correlations.…”
mentioning
confidence: 99%